A new fairy armadillo (Cingulata, Chlamyphoridae) from the Late Miocene of Argentine Pampas : first fossil record of the most enigmatic Xenarthra - Barasoain, Darío Daniel (2019)
Fil: Barasoain, Darío Daniel. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.